Developing a framework for improving coordination in the provision of agricultural support services to farmers in Oshikoto region Namibia - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.